Tailoring the DNA SAM surface density on different surface crystallographic features using potential assisted thiol exchange. (20th January 2018) - Leung, Kaylyn K.; Gaxiola, Andrea Diaz; Yu, Hua-Zhong; Bizzotto, Dan
Abstract: The influence of surface crystallography and applied potential on the thiol-exchange procedure to create mixed alkylthiol DNA SAMs is detailed. A single crystal gold bead and fluorophore labeled thiol modified DNA were used to characterize the resulting surface modifications. The thiol-exchange occurs with different efficiencies on the low index planes (111, 100, 110) as compared to 311 and 210. Positive applied potentials (>0/SCE) result in 10 × higher coverage than when compared to deposition at the open circuit potential (OCP) over the same 60 min time period. Negative potentials ( < 0/SCE) resulted in less uniform coverage with the 111 facet being significantly modified. The electrolyte used during the deposition was a 10 mM TRIS Buffer with 100 mM NaCl 500 mM MgCl 2 . The influence of [ Cl − ] was studied showing it had a significant impact on the thiol-exchange at the positive potentials, where higher [ Cl − ] resulted in higher DNA coverages and a more uniform coverage across the multi-crystalline surface. The local environment of the thiol-exchanged DNA SAMs were compared for different regions on the surface using potential driven DNA reorientation modulating the fluorescence intensity. These results showed a common behaviour from all surfaces suggesting that the DNA SAMs prepared by thiol-exchange were consistently prepared with a variable surface concentration controlled by potential and time. Graphical abstract: Image 1